The Synergistic Impact of Leadership and Emotional Intelligence on Employee Performance: Evidence from Nepal - Thapa, Ashish (Apex Journal of Business and Management, 2026)
Leadership and emotional intelligence (EI) are pivotal in driving employee performance in modern organizations. Leadership directs, motivates, and aligns goals, while EI equips leaders to navigate emotions in interactions. This study investigates their combined impact on performance in Nepalese organizations, addressing a research gap in empirical evidence on this synergy. Employing a quantitative design, data were gathered via structured questionnaires from employees and managers in commercial banks, IT firms, and service sectors in Nepal. Instruments measured leadership behaviors, EI dimensions (self-awareness, empathy, relationship management), and performance (task and contextual). Analyses included correlation, multiple regression, and moderation tests. Results show leadership positively affects performance; EI independently boosts outcomes. Critically, EI moderates this link, amplifying leadership's impact. Emotionally intelligent leadership thus heightens motivation, engagement, and performance. Findings advocate embedding EI in leadership training to enhance organizational effectiveness in Nepal.